IMPACT STUDY ON THE TRAINING SERIES ON GUEST RELATION: A BANNER PROGRAM OF BS TOURISM OF THE UM COLLEGE OF HOSPITALITY EDUCATION - Kiven Olivar; Clarence Joy D. Alcaraz (Journal for ReAttach Therapy and Developmental Diversities, 2024)
This paper measures the effectiveness of "The Training Series on Guest Relations Skills" program of the College of Hospitality Education Tourism Management Program of the University of Mindanao using a pretest-posttest approach. Further, the study determined the satisfaction of the beneficiaries with the implementation of the activities relative to the program. The study utilized a descriptive – comparative research design with 30 employees of D'Leonor Inland Resort and Adventure Park, who were beneficiaries of the program, participating in the study using complete enumeration. Results revealed that the Training Series on Guest Relations Skills program of Tourism Management was effective, suggesting that the program implementer has achieved the program's desired outcomes. Essentially, the program implementation is satisfactory and has reached the objectives for which it was designed.